1983
DOI: 10.1090/s0002-9939-1983-0691291-0
|View full text |Cite
|
Sign up to set email alerts
|

An effective version of Hall’s theorem

Abstract: Abstract. Manaster and Rosenstein [1972] constructed a recursively bipartite highly recursive graph that satisfies Hall's condition for a bipartite graph to have a matching, but has no recursive matching. We discuss a natural extension of Hall's condition which assures that every such graph has a recursive matching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The next lemma means that it is actually equivalent to sans-serifWKL over RCA0. Lemma sans-serifRCAsans-serif0[B,G,normalH]WKL, i.e., the following assertion implies sans-serifWKL over RCA0: If R(B,G) is a bipartite graph which is B,G‐highly recursive and satisfies the expanding Hall condition, then R(B,G) has a solution. Proof We extend Kierstead's proof of [, Theorem 5] to show this lemma. We reason in RCA0.…”
Section: Marriage Theorems With Expanding and Recursive Expanding Halmentioning
confidence: 94%
See 3 more Smart Citations
“…The next lemma means that it is actually equivalent to sans-serifWKL over RCA0. Lemma sans-serifRCAsans-serif0[B,G,normalH]WKL, i.e., the following assertion implies sans-serifWKL over RCA0: If R(B,G) is a bipartite graph which is B,G‐highly recursive and satisfies the expanding Hall condition, then R(B,G) has a solution. Proof We extend Kierstead's proof of [, Theorem 5] to show this lemma. We reason in RCA0.…”
Section: Marriage Theorems With Expanding and Recursive Expanding Halmentioning
confidence: 94%
“…Kierstead [, Theorem 5] showed that [normalB,normalG,H] does not hold in the least ω‐model of RCA0, while Hirst [, Theorem 2.3] showed that it is provable in WKL0. The next lemma means that it is actually equivalent to sans-serifWKL over RCA0.…”
Section: Marriage Theorems With Expanding and Recursive Expanding Halmentioning
confidence: 99%
See 2 more Smart Citations
“…To find a matching containing a given set of vertices, we have the following interesting result. Proposition 1.3.2 (Kierstead [316]) Let G be a graph and T the set of vertices of degree ∆(G). If G[T ] is a bipartite subgraph, then there exists a matching in G saturating all vertices of T .…”
Section: Matchings In Non-bipartite Graphsmentioning
confidence: 99%